PENDEKATAN EMOTIONAL DEMONSTRATION DALAM PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT PADA REMAJA UNTUK PENCEGAHAN STUNTING - farida wahyu ningtyias; Amanda Cynthia Margaretta; Auraning Mustika Hima Wardhani; Julianda Setyawati; Catryna Alfaidah; Marshanda Sofi Permatasari; Rahma Azizah; Elok Kholwatul Jannah (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2026)
According to data from the Bondowoso District Health Office in 2022, there were 53 cases of stunting incidents among toddlers reported in the Curahdami District. One of the contributing factors to the occurrence of stunting in Curahdami is the high incidence of diarrhea due to unhealthy living behaviors, such as the community's habit of bathing in rivers and using river water for daily needs, as well as the lack of handwashing practices with soap, both before handling food, after defecation, and after activities.There is a need to raise adolescents' awareness of the negative impacts of bathing in rivers on health, which can lead to infectious diseases and increase the risk of stunting. The methods used were lectures and emotional demonstration, an interactive approach that involves emotional and psychological aspects of participants. The activity was conducted once on December 7, 2024, at MTs Ukhuwah Islamiyah, Curahdami Subdistrict, Bondowoso Regency, involving 18 eighth-grade students. The effectiveness of the activity was evaluated by measuring students’ knowledge levels using pre-test and post-test questionnaires. The results showed an improvement in students’ knowledge regarding the negative health impacts of bathing in rivers. Students’ understanding of the importance of handwashing with soap and running water also increased after the activity. The average percentage of correct answers increased from 40.5% in the pre-test to 89.5% in the post-test. In conclusion, this activity successfully enhanced adolescents’ awareness in adopting clean and healthy living behaviors as an effort to prevent stunting.